PSV-21 The behavior, physiology and immunity of pregnant sows housed in individual crate with different frequency of sham-chewing. (30th November 2020) - Yi, Ran; Zhang, Runxiang; Liu, Honggui; Li, Xiang; Bao, Jun
Abstract: The sham-chewing behavior indicates the poor welfare of sows and quite frequently occurs in confined environment. To evaluate the behavior, physiology and immunity of pregnant sows with different frequency of sham-chewing, 63 sows (Large White × Landrace) housed in individual gestation crate were divided into the high (H), middle (M) and low (L) frequency groups based on the sham-chewing frequency analyzed by Hierarchical cluster using SPSS 20.0 systems. The behavioral data, including sham-chewing, standing, sitting, ventral lying, lateral lying, bar-biting and rooting, was observed in early, middle and late pregnancy (days 26–27, 61–62 and 91–92) of the sows. Serum CRP, IL-10 and IFN-γ contents were detected by enzyme-linked immunosorbent assay (ELISA). The results showed that the frequency of sham-chewing significantly reduced with the increase of the pregnancy period (P < 0.001) and the difference among three groups was significant in early and middle pregnancy (P < 0.001). Standing behavior in Group H and M decreased significantly (P = 0.004; P = 0.020). Sitting, ventral lying and lateral lying behaviors were significantly lower in early pregnancy than those in late pregnancy (P < 0.05). In late pregnancy, bar-biting of Group H was significantly increased (P = 0.018), while rooting was decreased (P = 0.033). The CRP level was significantly higher in Group H than L in middle pregnancy (P = 0.031). The IFN-γ level was significantly lower in Group H (P < 0.05). In late pregnancy, IL-10 level was significantly higher in group H and M than L (P < 0.05). Therefore, the pregnant sows with different frequency of sham-chewing showed differences in standing and lateral lying behaviors. The expression of sham-chewing reflects the higher level of stress and lower level of immunity and may indicate the maladaptation of pregnancy sows to the confined environment.